DESIGNING A CLOSED-LOOP SUPPLY CHAIN NETWORK AND PROVIDING A MULTI-OBJECTIVE MATHEMATICAL MODEL TO SELECT A THIRD-PARTY LOGISTICS COMPANY AND SUPPLIER SIMULTANEOUSLY - Jafarzadeh-Ghoushchi, Saeid; Hushyar, Iman (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
In this study, a closed-loop supply chain network is designed. The solution for the applied model is determined in two phases. First, third-party logistics (3PLs) and external suppliers are selected by using grey theory. The outputs are the weight of 3PLs and suppliers. Second, a multi-objective mixed-integer linear programming model (MOMILP) is proposed. Through this model, 3PLs and suppliers are selected, and the optimal amount of returns to 3PLs and parts purchased from suppliers are determined. The proposed model considers the simultaneous selection of 3PLs and suppliers. The contribution of this study is a novel configuration of the multi-stage, multi-period, multi-product closed-loop supply chain network and 3PL and supplier selection by using grey theory, wherein a MOMILP is developed to implement the network and partner allocation. The supplier hub is utilized in the proposed network, which has rarely been accomplished in the previous literature. Finally, a numerical example is provided.